THE CONCEPT OF FORMING PROFESSIONAL COMPETENCIES OF SPECIALISTS IN INFORMATIONAL TECHNOLOGIES AND CYBER SECURITY - Юдін, Олександр Костянтинович; Матвійчук-Юдіна, Олена Василівна (Science-based technologies, 2019)
The article analyzes the specifics of the formation of training for the specialists in information technologies and cyber security in accordance with the world system of standardization of the information technology industry (IT) and national requirements of the state. A comparative analysis was carried out and the content of competence creation based on the American industrial model and the European competence framework of information and communication technology specialists is disclosed. The nowadays specifics and trends of development and formation of educational standards of academic and professional orientation are determined. It is shown that these trends are characterized by the requirements of the IT industry services, and also determine the requirements of industry, necessary knowledge, skills and capacities of specialists in the labor market. The main features of the formation of competencies of information technology and cybersecurity specialists are revealed. The conceptual issues of the possibility of using the European competence framework for information and communication technology (ICT) specialists, in particular, the European e-Competence Framework (e-CF) and the American platform model as a system-based foundation for training personnel in IT and cybersecurity, are considered. Close attention is paid to the international general-purpose approaches of standardization of educational services, levels of competences in accordance with professional requirements for specialists in the system of classification of positions. The classification of academic and professional competencies of specialists who must ensure a high level of quality of a wide range of services in the field of information technology and cyber security, information and communication systems or directly organizations or institutions is determined. It is shown that this approach of forming the basis of skills and abilities allows using the fundamental professional knowledge and the multilevel principle of classification of the basic competencies in accordance with world standardization system in the development of domestic educational and professional programs and qualification requirements. The perspectives of research, that consist of the determination of integrity in career development, personnel management in the field of information technologies, monitoring of demand and supply in the labor market, are outlined; along with the correspondence of national and corporate competencies, qualifications, professional certification, etc. A comparative analysis was carried out and it was shown that the above mentioned conceptual principles of training for specialists should become the basis for the formation of the national classification of the positions in the sector of information technology and cybersecurity It has been determined that the classification of positions should be based on the specific clusters of competencies in the field of information and communication technologies and the industrial model of the USA. On the basis of the conducted researches, perspectives and approaches have been defined, concerning the methodology of forming the competencies of specialists for the educational branch of information technologies and cybersecurity. The above-mentioned conceptual approach will allow the domestic education system and the universities of the country that train IT professionals to successfully realize and implement the educational processes of integration into the service market, as well as to ensure the creation of common educational standards and competency classes, in order to improve the quality of education and the results of training.